Pengembangan Keterampilan Berpikir Kritis Siswa Sekolah Dasar Melalui Model Pembelajaran Inkuiri - Dilla, Marsha (Indonesian Journal Publisher, 2024)
Critical thinking skills are important to develop early on for elementary school students so they are able to solve problems well. This study aims to determine the effectiveness of implementing inquiry learning model in developing critical thinking skills of elementary school students. This quasi-experimental designed study involved grade students divided into experimental group (inquiry model) and control group (conventional learning). Pretest and posttest instruments were used to measure students' critical thinking skills, then will be analyzed. The results showed that the improvement of critical thinking skills of experimental group students was significantly higher than the control group. This proves that inquiry learning model is effective for developing critical thinking skills of elementary school students. Therefore, it is recommended for teachers to implement inquiry learning models to stimulate and improve students' critical thinking abilities.